THE URGENCY OF DIGITAL LITERACY TO MINIMIZE THE SSPREAD OF RELIGIOUS HOAXES AMONG STUDENTS OF ISLAMIC UNIVERSITY IN PANDEMIC COVID-19 - Naomi Ainun Hasanah (Muẚṣarah: Jurnal Kajian Islam Kontemporer, 2021)
The development of information and communication technology increase the accessibility to get information through digital devices. In addition, the spread of Covid-19 in these few years increases the need to use digital devices and applications to expand knowledge and sharpen understanding among students of Islamic universities. However, the spread of hoax information related to religious understanding increases. A lack of basic religious understanding can trigger the spread of excessive hoaxes. This research aims to reveal the urgency of digital literacy and religious understanding, especially for students in Islamic universities. The Method of this research is Library Research. This research shows that digital literacy and religious understanding are essential to minimize the entry of extreme ideas and the spread of hoaxes. Therefore, every student of Islamic university should increase digital literacy skills and religious understanding through other authoritative sources